Oxytocin attenuates phencyclidine hyperactivity and increases social interaction and nucleus accumben dopamine release in rats - Kohli, Shivali; King, Madeleine V.; Williams, Stuart; Edwards, Adele; Ballard, Theresa M.; Steward, Lucinda J.; Alberati, Daniella; Fone, Kevin C.F. (Nature Publishing Group, 2018)
The pituitary neuropeptide oxytocin promotes social behavior, and is a potential adjunct therapy for social deficits in schizophrenia and autism. Oxytocin may mediate pro-social effects by modulating monoamine release in limbic and cortical areas, which was investigated herein using in vivo microdialysis, after establishing a dose that did not produce accompanying sedative or thermoregulatory effects that could concomitantly influence behavior. The effects of oxytocin (0.03-0.3mg/kg s.c.) on locomotor activity, core body temperature and social behavior (social interaction and ultrasonic vocalisations) were examined in adult male Lister-hooded rats, using selective antagonists to determine the role of oxytocin and vasopressin V1A receptors. Dopamine and serotonin (5-HT) efflux in the prefrontal cortex (PFC) and nucleus accumbens (NAc) of conscious rats were assessed using microdialysis. 0.3mg/kg oxytocin modestly reduced activity and caused hypothermia but only the latter was attenuated by the V1A receptor antagonist, SR49059 (1mg/kg i.p.). Oxytocin at 0.1mg/kg, which did not alter activity or temperature, significantly attenuated PCP-induced hyperactivity and increased social interaction between unfamiliar rats without altering the number or pattern of ultrasonic vocalisations. In the same rats, oxytocin (0.1 mg/kg) selectively elevated dopamine overflow in the NAc (F(1, 12)=7.983, P=0.0153), but not PFC, without influencing 5-HT efflux. Systemic oxytocin administration attenuated PCP-induced hyperactivity and increased pro-social behavior without decreasing core body temperature and selectively enhanced NAc dopamine release, consistent with activation of mesocorticolimbic circuits regulating associative/reward behavior being involved. This highlights the therapeutic potential of oxytocin to treat social behavioral deficits seen in psychiatric disorders such as schizophrenia and autism.